2004
DOI: 10.1111/j.1080-8620.2004.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Equity Dilution: An Alternative Perspective on Mortgage Default

Abstract: Empirical research on mortgage default in the single-family market has focused on the value of the borrower's put option using house price indices to estimate contemporaneous loan-to-value ratio or the probability of negative equity. But since the borrower possesses the option to increase leverage by taking on additional debt secured by junior liens subsequent to loan origination (a phenomenon termed here equity dilution), even a perfect house price adjustment cannot be expected to accurately measure changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Another explanation is a lower degree of mobility for such households, which would be consistent with the results in Goldberg and Harding (2003). Finally, low‐income households may take out additional mortgages more frequently, and high LTV ratios (including all mortgage debt) may prevent refinancing, as discussed in Lacour‐Little (2004).…”
Section: Literature Reviewsupporting
confidence: 62%
“…Another explanation is a lower degree of mobility for such households, which would be consistent with the results in Goldberg and Harding (2003). Finally, low‐income households may take out additional mortgages more frequently, and high LTV ratios (including all mortgage debt) may prevent refinancing, as discussed in Lacour‐Little (2004).…”
Section: Literature Reviewsupporting
confidence: 62%
“…Another explanation is a lower degree of mobility for such households, which would be consistent with the results in Goldberg and Harding (2003). Finally, low-income households may take out additional mortgages more frequently, and high loan to value ratios (including all mortgage debt) may prevent refinancing, as discussed in Lacour-Little (2004). We find credit history is an also an important predictor of prepayment.…”
Section: Introductionsupporting
confidence: 80%
“…More recent papers include LaCour‐Little () which argues that a borrower's postorigination home equity borrowing dilutes equity increasing the risk of default on the senior debt. In a working paper, LaCour‐Little, Rosenblatt and Yao () report that roughly 80% of Southern California borrowers facing foreclosure during 2006–2008 had at least one junior lien outstanding, suggesting that junior lien borrowing may increase foreclosure risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that junior lien lending through home equity loans is related to the increase in household leverage (Mian and Sufi ) and the decline in personal savings (Greenspan and Kennedy ). Increased debt usage through home equity lending can also dilute equity in a borrower's home, thereby increasing the default risk of first mortgage and magnifying the impact of declining house prices on default and foreclosure rates (LaCour‐Little ). According to a recent CoreLogic negative equity report (CoreLogic ), nationwide aggregate negative equity reached $699 billion in the third quarter of 2011.…”
mentioning
confidence: 99%